Genetics professionals' attitudes toward prenatal exome sequencing. Issue 2 (19th March 2019) - Brew, Casey E.; Castro, Brian A.; Pan, Vivian; Hart, Alexa; Blumberg, Bruce; Wicklund, Catherine
Abstract: Prenatal exome sequencing (ES) currently has limited use in the clinical setting, but research suggests that it has added diagnostic utility over karyotyping and array techniques for prenatal diagnosis of fetuses presenting with ultrasound abnormalities. The purpose of this study was to assess the attitudes of genetics professionals toward the clinical implementation of prenatal ES in order to guide development of professional guidelines. A survey was developed using themes identified in previous qualitative studies and was distributed to members of the American College of Medical Genetics and Genomics (ACMG), the American Society of Human Genetics (ASHG), and the National Society of Genetic Counselors (NSGC). A total of 498 participants completed some portion of the survey. There was consensus among participants that there would be clinical utility of prenatal ES when used for diagnosis, pregnancy management, and termination decisions. The majority also agreed that prenatal ES was distinct from its current use in the pediatric and adult settings. There were many areas of contention regarding which types of results should be returned to families and whether or not the current ACMG guidelines for return of incidental findings should also apply to the prenatal setting. Overall, professional guidance is needed to address the continuing concerns surrounding prenatal ES as its utilization in this setting is expected to grow.